Correction: Devices and techniques for bariatric and metabolic endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) technical and technology review - Boškoski, Ivo; Matteo, Maria Valeria; Shamah, Steven; Dayyeh, Barham K. Abu; Bove, Vincenzo; Siena, Martina De; Huberty, Vincent; Maselli, Roberta; Perretta, Silvana; Pontecorvi, Valerio; Stier, Christine; Sharaiha, Reem Z.; et al. (Endoscopy, 2025)
Thieme E-Books & E-Journals